Konsep Hukum Archimedes Melalui Eksperimen Daun Bunga Sepatu untuk Perkembangan Sains Anak Usia Dini - Pujiniarti, Yayu Bondan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The concept of Archimedes' law through hibiscus leaf experiments can develop science in early childhood. the purpose of this study in general is to develop science in early childhood, the specific goal is to develop cognitive, social-emotional, language, physical-motor, religious abilities. This research uses an experimental method by taking data in the field called descriptive qualitative by taking data sources from observation techniques. The results of experiments or hibiscus leaf experiments can develop science in Early Childhood, this is shown by hibiscus leaf experiments that are associated with Archimedes' law, namely the concept of floating and floating sinking. Objects will float if the density of liquid is greater than the density of objects so that objects are above the surface of liquids, objects will float if the density of liquid is equal to the density of objects so that the position of objects is above the base of liquid and below the surface of liquids, objects will sink if the density of liquid is less than the density of objects so that the position of objects is at the bottom of the liquid place. The results of this experiment, easy, inexpensive, fun and educational for early childhood. This shows that the application of the concept of Archimedes' law through hibiscus leaf experiments can develop science in Early Childhood